Смех (в) „фантастической трилогии” Федорa Достоевского - Muránska, Natália (Studia Rossica Posnaniensia, 2024)
Among the works included in A writer’s diary by Fyodor Dostoevsky, literary scholars point out the “fantastic trilogy” – The dream of a ridiculous man, A gentle creature, and Bobok. Three heroes of Dostoevsky, three outsiders who are in conflict with their environment – a ridiculous man, an underground man and a drunken writer – are the main characters of the “fantastic trilogy”. The article examines the poetological principle of laughter, on which the ontology of Dostoevsky’s artistic world is based. In the aforementioned three short stories three varieties of laughter are identified: 1) laughter as a result of realizing the incompatibility of the truth of the heart with the necessity to live here and now (The dream of a ridiculous man, 1877); 2) laughter as Bakhtin’s genre-forming principle: muffled laughter, that is, laughter that is not heard, which is an expression of the impossibility of resolving a dispute, the impossibility of saying the last word about a problematic world, about its dual truthfulness – the truth of the heart and the truth of the mind (A gentle creature, also titled as The meek one, 1876); 3) a type of parodic laughter, or laughter that laughs out loud (Bobok, 1873).